RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE OF ADOLESCENTS TOWARDS HIV/AIDS PREVENTION AT YPK IMMANUEL HIGH SCHOOL MANOKWARI - Mansa, Gidion; Ardiansyah, Fazrin; Nuryanti, Yayuk (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Global HIV Number In 2023, there will be 39.9 million people worldwide living with HIV. Of these, 38.6 million are adults and 1.4 million are children. Global HIV-related deaths. In 2023, 630,000 people will die from HIV-related causes worldwide. HIV cases in Indonesia. The estimate of PLHIV in West Papua Province in 2024 is 12,050 and PLHIV who have been found until January 2024 are 4,681 people or around 39%, still very far from the fast track target of 95%. To determine the relationship between knowledge and attitudes of adolescents towards HIV/AIDS prevention at SMU YPK Immanuel Manokwari 2024. This type of research is a quantitative research type with a quasi-experimental method or "Quasi Experiment". The design used in this study is the One-Group Pretest-Posttest Design. The sample consisted of 60 students, using nonprobability sampling with purposive sampling. Where students will be measured for knowledge and attitudes about HIV/AIDS prevention after the pre-test will be given treatment/counseling about HIV/AIDS prevention, after that will be given a post-test questionnaire. The results of the study obtained an increase in knowledge and attitudes after treatment or counseling about HIV/AIDS prevention and with the Wilcoxon test and obtained a value (α <0.05).